A Single Dose of Oral ATP Supplementation Improves Performance and Physiological Response During Lower Body Resistance Exercise in Recreational Resistance-Trained Males - Freitas, Marcelo C. [UNESP]; Cholewa, Jason M.; Gerosa-Neto, Jose [UNESP]; Gonçalves, Daniela C.; Caperuto, Erico C.; Lira, Fábio S [UNESP]; Rossi, Fabrício E (Wolters Kluwer, 2019)
Freitas, MC, Cholewa, JM, Gerosa-Neto, J, Gonçalves, DC, Caperuto, EC, Lira, FS, and Rossi, FE. A single dose of oral ATP supplementation improves performance and physiological response during lower body resistance exercise in recreational resistance-trained males. J Strength Cond Res 33(12): 3345-3352, 2019-The aim of this study was to investigate the acute effect of adenosine-5'-triphosphate (ATP) supplementation on performance and physiological responses during resistance exercise in recreationally resistance-trained males. Eleven men (age = 27.5 ± 5.5 years, mass = 83.4 ± 9.8 kg, height = 182 ± 0.04 cm) completed 2 randomized, double-blind trials: ATP supplement condition (ATP = 400 mg) or a placebo condition. Thirty minutes after supplement consumption, subjects performed 4 sets of half-squats until momentary muscular failure at 80% of the 1 repetition maximum with 2 minutes of recovery between sets. The total number of repetitions, blood pressure, heart rate, blood lactate, and oxygen consumption were evaluated. The total weight lifted were higher for the ATP condition compared with placebo (Placebo = 3,995.7 ± 1,137.8, ATP = 4,967.4 ± 1,497.9 kg; p = 0.005). Heart rate was higher at set-4 for ATP compared with placebo (p < 0.001) and oxygen consumption during exercise was greater for ATP (p = 0.021). There were no differences between conditions for lactate and blood pressure. In summary, a single oral dose of ATP supplementation improved lower-body resistance training performance and energy expenditure in recreational resistance-trained males.